Development of usable mobile application and its effectiveness in health promotion and education on colorectal cancer - Marzuki, Muhamad Fadhil Mohamad (2019)
Background: Lack of knowledge and awareness on colorectal cancer is one of the barriers for screening participation. With the advancement of technology today, people’s preference of information search has shifted from reading the printed material such as pamphlet to more interactive media such as mobile application. Therefore, a usable mobile application can be one of the methods in health promotion and education to improve the knowledge and attitude on colorectal cancer hence increase the screening and detection of colorectal cancer. Objectives: The objectives were to determine the factors associated with colorectal cancer in Malaysia, to assess the usability of the mobile application as a method for health promotion and education on colorectal cancer, and to compare the mean percentage score of knowledge and mean percentage score of attitude on colorectal cancer between intervention and control group with consideration of time pre and post intervention. Methodology: This study was conducted in two phases. Phase one was a case-control study using data from the National Cancer Patient Registry - Colorectal Cancer (NCPR-CC) and National Health and Morbidity Survey (NHMS) 2015 to achieve the first objective. The analysis was done using multiple logistic regression. In phase two, a mobile application named ColorApp (Colorectal Cancer Application) was developed. Its usability and effectiveness were tested in a quasi-experimental study involving 100 participants from selected Komuniti Sihat Pembina Negara (KOSPEN) localities in Kota Setar district as the intervention group, and Kuala Muda district as the control group to achieve objective 2, 3 and 4. The analysis was conducted using One sample T-test for objective 2 and Repeated Measures Analysis of Covariances (RM ANCOVA) for objective 3 and 4. Result: People at the age group between 50 to 70 years old have 10.56 times higher odds (95% CI: 8.66, 12.88) and people aged above 70 years old have 39.79 times higher odds to develop colorectal cancer (95% CI: 31.86, 49.69) compared to people less than 50 years old. A significant association also found among Chinese (Adj. OR: 3.51; 95% CI: 3.01, 4.08), smokers (Adj. OR: 2.18; 95% CI: 1.88, 2.52) and diabetic patient (Adj. OR:1.32; 95% CI: 1.11, 1.56). The ColorApp’s mean (SD) usability score was 72.9(11.52) which is significantly higher than the standard usability score of 68.0 indicating a usable mobile application. There was no significant difference in baseline knowledge and attitude between intervention and control groups. There was overall significance difference of mean knowledge score between intervention and control group [F (1,95) = 19.81; p < 0.001]. However, there was no overall significance difference of mean attitude score between intervention and control group [F (1,95) = 0.36, p = 0.550]. Conclusion: A mobile application is a way forward for health promotion and education, particularly in the prevention and early detection of colorectal cancer.